Gospell-Glory proclaymed before ye sonnes of men, in ye visible and invisible worship of God. Wherein the mysterie of God in Christ, and his royall, spirituall government over the soules and bodies of his saints, is cleerly discovered, plainly asserted, and faithfully vindicated, against the deceiver and his servants, who endeavour the cessation thereof, upon what pretence soever. / By Edward Drapes, an unworthy servant in the gospell of Christ. [electronic resource] :
Summary goes here